การวิเคราะห์ข้อมูลแบบหลายมิติเพื่อหาสาเหตุการทำงานซ้ำของกระบวนการปรับตั้งมุมล้อรถยนต์ - ปฐมชัย สุวรรณปิณฑะ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The problems of reworks in the car assembly process of the case study plant occurred when cars that had completed the assembly process did not pass the quality inspection standards of the wheel alignment process and needed rework. Reworking increased the workload of the wheel alignment process. This often caused overtime work in order to meet production targets. Over-time work added production cost and exhausted workers. Since the wheel alignment process was already the bottleneck of the assembly line, it would also be a restriction when the company would try to increase its production capacity in the future. Although, the company collected wheel alignment data of every car, it did not make any use of it. This research attempted to analyze the data with multi-dimensional data model in order to find the causes of the wheel alignment problems. The analysis asked questions on relationships between problems and factors that might cause them. When the analysis revealed the real causes of the problems, effective solutions were proposed. After implementing the proposed solutions for two months, it was found that the reworks of the wheel alignment process reduced significantly from 4.99 percent to 3.9 percent.